Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE), 2013 2013
DOI: 10.7873/date.2013.295
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Analytical Nonlinear Models from Analog Circuits by Recursive Vector Fitting of Transfer Function Trajectories

Abstract: Abstract-This paper presents a technique for automatically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In order to capture strongly nonlinear dynamics, the nonlinear part is implemented as a piecewise combination of linear functions. Other nonlinear function approximations of the residues can be found in [18]- [20]. The time-domain representation of the Wiener-TFT approximation is found by piecewise integration of the residues (13) The constant is found by comparing the system output to the output of the model with .…”
Section: Piecewise Tft Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to capture strongly nonlinear dynamics, the nonlinear part is implemented as a piecewise combination of linear functions. Other nonlinear function approximations of the residues can be found in [18]- [20]. The time-domain representation of the Wiener-TFT approximation is found by piecewise integration of the residues (13) The constant is found by comparing the system output to the output of the model with .…”
Section: Piecewise Tft Modelingmentioning
confidence: 99%
“…In this paper, a novel method is proposed for the variability analysis of complex nonlinear systems based on the calculation of the PC expansion of the Transfer Function Trajectory (TFT) [18]- [20] model of the system under study, indicated below as the PC-TFT model. The proposed technique is particularly suitable to model RF nonlinear circuits thanks to the modeling power of the parametric vector fitting (VF) algorithm [21]- [23] employed by the TFT method.…”
Section: Introductionmentioning
confidence: 99%
“…In [4], the authors propose to extract behavioral models directly from the netlists by processing simulation results into transfer function trajectories. The method was demonstrated on a small circuit with minimal speedup and the approach is not always automatable.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of the stochastic macromodeling technique [18] is to express the time-domain variability of a nonlinear system which depends on a vector of normalized random variables ξ via the PC expansion [3]- [8] of the corresponding TFT model [19]- [21] implemented as a multi-channel Wiener system with a linear time-invariant block at the input and a nonlinear readout map. The resulting model is called PC-TFT model and can be expressed as [18]:…”
Section: Stochastic Macromodeling Of Nonlinear Systemsmentioning
confidence: 99%
“…Also, the PC methodology has been proposed for the variability analysis of nonlinear electronic circuits [15]- [18]. Recently in [18], a method has been proposed for the variability analysis of complex nonlinear systems based on the calculation of the PC expansion of Transfer Function Trajectory (TFT) [19]- [21] models. This method can be applied to a broad range of nonlinear circuits thanks to the modeling power of the TFT and it offers the efficiency and accuracy of the PC approach in performing the variability analysis.…”
Section: Introductionmentioning
confidence: 99%